The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/soin.12161
|View full text |Cite
|
Sign up to set email alerts
|

School Spillover and College Student Health

Abstract: This article uses a stress carryover perspective to examine the association between school spillover and mental and behavioral health outcomes among college undergraduates. School spillover occurs when the obligations and pressures of student life extend into other domains through shared behaviors or stress. The sample (N = 250) consisted of undergraduate students between the ages of 18 and 29 enrolled at a midsized midwestern university. Findings showed that on average, students reported a moderate level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Using experimental testing and regression analysis, the authors identified the variables influencing the use of mental health services, such as intention to look for help, social support, and self-assessment of mental health. Based on the theory of stress transmission, literature [22] investigated the connection between students' psychological and behavioral well-being in higher education and school spillover effects. The educational spillover effect and unpleasant feelings like restlessness and irritation were found to have a favorable correlation, as revealed by a study conducted on 250 children.…”
Section: Introductionmentioning
confidence: 99%
“…Using experimental testing and regression analysis, the authors identified the variables influencing the use of mental health services, such as intention to look for help, social support, and self-assessment of mental health. Based on the theory of stress transmission, literature [22] investigated the connection between students' psychological and behavioral well-being in higher education and school spillover effects. The educational spillover effect and unpleasant feelings like restlessness and irritation were found to have a favorable correlation, as revealed by a study conducted on 250 children.…”
Section: Introductionmentioning
confidence: 99%
“…They need to face reselection of values and rebuilding of personality. They also face enormous pressures related to social selection and possible social elimination (Mei, Chai, Li, & Wang, 2017;Pedersen, Swenberger, & Moes, 2017;Tupler, Hong, Gibori, Blitchington, & Krishnan, 2015).…”
Section: Introductionmentioning
confidence: 99%